Uses of Stevia - A Review (International Journal of Food and Nutritional Sciences, 2022)
A naturally occurring, calorically-free sweetener with greater sweetness than sucrose is the tiny perennial shrub Stevia rebaudiana Bertoni. Stevia is also known as honey yerba, sweet leaf, sugar leaf, and honeyleaf. Since ancient times, it has been utilised as a traditional medicine and a bio-sweetener all over the world. Professionals may suggest stevia use in their clinical settings as a crucial addition to lowering a person's risk of developing dental caries.